1997
DOI: 10.1007/s002620050392
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-peptide-pulsed dendritic cells isolated from spleen or cultured in vitro from bone marrow precursors can provide protection against tumor challenge

Abstract: Dendritic cells (DC) purified from murine spleen or generated in vitro from bone marrow precursors were compared for their respective abilities to stimulate T cell responses and provide tumor protection in vivo. In vitro incubation with synthetic tumor peptide conferred on both DC populations the ability to induce proliferation of tumor-peptide-specific T cells in vitro. Spleen DC were reproducibly about twofold more effective than bone-marrow-derived DC in this assay. Both DC populations could also induce cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Genetically modified or peptide-pulsed DC can generate immunity to established tumors or tumor challenge (29,30). In this study, we report the effect of combined intratumor injection of DISC/mGM-CSF and syngeneic bone marrow-derived DC on the growth of s.c. CT26 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Genetically modified or peptide-pulsed DC can generate immunity to established tumors or tumor challenge (29,30). In this study, we report the effect of combined intratumor injection of DISC/mGM-CSF and syngeneic bone marrow-derived DC on the growth of s.c. CT26 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, CFSE ϩ DC loaded with the MHC class I-binding peptide LCMV 33-41 were administered to mice that had been injected s.c. in the flank 7 days before with 10 5 DC alone or with 10 5 DC loaded with the same LCMV 33-41 peptide. The 7-day interval was chosen because our previous studies have shown that Ag-specific T cell expansion is maximal at this time (22); also, resistance to challenge with LCMV 33-41 -expressing tumors can be demonstrated (17). In addition, "memory" recipients were also used.…”
Section: Clearance Of Ag-loaded DC Is Accelerated In the Presence Of mentioning
confidence: 99%
“…For these studies we used the tumor cell line LL-LCMV, a Lewis lung carcinoma expressing the LCMV 33-41 epitope (17). All mice were preimmunized s.c. in the flank with DC loaded with OVA 257-264 to induce OVA 257-264 -specific CTL responses.…”
Section: Ctl-mediated Clearance Of Tumor Ag-loaded DC From the Lymph mentioning
confidence: 99%
“…B16.F10 melanoma expressing gp33 (B16.gp33, [31]) and Lewis lung carcinoma expressing gp33 (LL-LCMV, [32]) were maintained in cIMDM containing 0.5 mg/mL Geneticin s (GIBCO, Auckland, New Zealand).…”
Section: Tumor Cell Linesmentioning
confidence: 99%
“…Mice were challenged with 2 Â 10 5 B16.gp33 cells or 1 Â 10 5 LL-LCMV cells in the left flank, and examined every 2-3 days to monitor tumor growth as described [32].…”
Section: Tumor Protectionmentioning
confidence: 99%